Effect of Dietary Canarium indicum L. on the Growth, Health, and Resistance of Asian Seabass Challenged with Vibrio alginolyticus - Taufiq Abdullah; Dinamella Wahjuningrum; Widanarni Widanarni (Jurnal Ilmiah Perikanan dan Kelautan)
Abstract